Does the application of vermicompost solid and liquid extracts influence the growth, N-nutrition and soil microbial diversity of the legume, Lupinus angustifolius? - Allardice, Roderick (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.